Exposure of Human CD8+ T Cells to Type-2 Cytokines Impairs Division and Differentiation and Induces Limited Polarization - Fox, Annette; Harland, Kim L.; Kedzierska, Katherine; Kelso, Anne (Frontiers in Immunology, 2018)
Effector CD8+ T cells generally produce type-1 cytokines and mediators of the perforin/granzyme cytolytic pathway, yet type-2-polarized CD8+ cells (Tc2) are detected in type-2 (T2) cytokine-driven diseases such as asthma. It is unclear whether T2 cytokine exposure during activation is sufficient to polarize human CD8+ T cells. To address this question, a protocol was developed for high-efficiency activation of human CD8+ T cells in which purified single cells or populations were stimulated with plate-bound anti-CD3 and anti-CD11a mAb for up to 8 days in T2 polarizing or neutral conditions, before functional analysis. Activation of CD8+ naïve T cells (TN) in T2 compared with neutral conditions decreased the size of single-cell clones, although early division kinetics were equivalent, indicating an effect on overall division number. Activation of TN in T2 conditions followed by brief anti-CD3 mAb restimulation favored expression of T2 cytokines, GATA3 and Eomes, and lowered expression of type-1 cytokines, Prf1, Gzmb, T-BET, and Prdm1. However, IL-4 was only weakly expressed, and PMA and ionomycin restimulation favored IFN-γ over IL-4 expression. Activation of TN in T2 compared with neutral conditions prevented downregulation of costimulatory (CD27, CD28) and lymph-node homing receptors (CCR7) and CD95 acquisition, which typically occur during differentiation into effector phenotypes. CD3 was rapidly and substantially induced after activation in neutral, but not T2 conditions, potentially contributing to greater division and differentiation in neutral conditions. CD8+ central memory T cells (TCM) were less able to enter division upon reactivation in T2 compared with neutral conditions, and were more refractory to modulating IFN-γ and IL-4 production than CD8+ TN. In summary, while activation of TN in T2 conditions can generate T2 cytokine-biased cells, IL-4 expression is weak, T2 bias is lost upon strong restimulation, differentiation, and division are arrested, and reactivation of TCM is reduced in T2 conditions. Taken together, this suggests that exposure to T2 cytokines during activation may not be sufficient to generate and retain human Tc2 cells.